KUALITAS SENSORIS DAN AKTIVITAS ANTIOKSIDAN KUE BAWANG YANG DIPERKAYA PASTA UMBI BIT MERAH (Beta vulgaris L.) - Rohaya, Syarifah; Asiah, Ida; Muzaifa, Murna (BPFP Faperta UNIB, 2023)
Shallots crisp is one type of traditional Indonesian food that is favoured by the wider community. Currently, public awareness of healthy food is increasing, including in choosing snacks. Red beetroot is a tuber plant that has the advantage of being a natural coloring agent and a source of antioxidants. Aims of this study were to determine the antioxidant activity and sensory test of shallots crips with the addition of beetroot paste at various concentrations. This study used a non-factorial Completely Randomized Design. The treatment used was making shallots crips using 200 g of flour added with a concentration of beetroot paste with a concentration of F1=20%, F2=30%, F3=40%, F4=50%, and F5=60%. Repetition was carried out 3 times to obtain 15 trials. The analysis carried out was the hedonic test, the description test on organoleptic including color, aroma, taste and texture as well as testing the antioxidant activity and water content of the Shallots cripss added with red beetroot paste. The results showed that the addition of red beetroot paste had a significant effect (p<0.05) on antioxidant activity, water content, description test and hedonic test for color, aroma, taste and texture. This research recommends F3 treatment as the best treatment alternative considering its antioxidant activity (58.26%); moisture content (3.40%); color description 4.44 (purplish red), onion and beetroot cake aroma description 3.52 (normal/typical), savory taste description 3.27 (normal/typical), texture description 3.29 (normal/typical) and hedonic with a color score of 3.99 (likes), aroma 3.81 (likes), taste 4.27 (likes) and texture 4.10 (likes).